Student–Community Collaboration in Empowering MSMEs: A Bazaar Program in Tungku Jaya Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Empowering Micro, Small, and Medium Enterprises (MSMEs) is crucial to fostering sustainable economic development in rural areas. Through the Community Service Program (KKN), university students actively engage in local development initiatives, including community-based bazaars that promote entrepreneurship and strengthen local economies. This study examines a one-day MSME bazaar held in Tungku Jaya Village as a collaborative effort between students and local residents to improve product promotion, expand market reach, and provide training in packaging, marketing strategies, and digital promotion. A Participatory Action Research (PAR) framework was employed, involving students, MSME owners, village officials, and community members in planning, implementation, and evaluation. Data were gathered through observation, interviews, questionnaires, and documentation. Results showed that 85% of MSME owners experienced sales growth, 70% reported increased confidence in marketing their products, and 90% expressed interest in holding similar events regularly. These findings demonstrate that student–community collaboration can serve as an effective model for rural MSME empowerment. The approach not only generated measurable economic benefits but also fostered sustainable community engagement, making it a replicable strategy for other rural contexts.